Carbohydrate depletion in roots impedes phosphorus nutrition in young forest trees. Issue 5 (1st January 2021) - Clausing, Simon; Pena, Rodica; Song, Bin; Müller, Karolin; Mayer‐Gruner, Paula; Marhan, Sven; Grafe, Martin; Schulz, Stefanie; Krüger, Jaane; Lang, Friederike; Schloter, Michael; Kandeler, Ellen; et al.
Summary: Nutrient imbalances cause the deterioration of tree health in European forests, but the underlying physiological mechanisms are unknown. Here, we investigated the consequences of decreasing root carbohydrate reserves for phosphorus (P) mobilisation and uptake by forest trees. In P‐rich and P‐poor beech ( Fagus sylvatica ) forests, naturally grown, young trees were girdled and used to determine root, ectomycorrhizal and microbial activities related to P mobilisation in the organic layer and mineral topsoil in comparison with those in nongirdled trees. After girdling, root carbohydrate reserves decreased. Root phosphoenolpyruvate carboxylase activities linking carbon and P metabolism increased. Root and ectomycorrhizal phosphatase activities and the abundances of bacterial genes catalysing major steps in P turnover increased, but soil enzymes involved in P mobilisation were unaffected. The physiological responses to girdling were stronger in P‐poor than in P‐rich forests. P uptake was decreased after girdling. The soluble and total P concentrations in roots were stable, but fine root biomass declined after girdling. Our results support that carbohydrate depletion results in reduced P uptake, enhanced internal P remobilisation and root biomass trade‐off to compensate for the P shortage. As reductions in root biomass render trees more susceptible to drought, our results link tree deterioration with disturbances in the P supply as a consequence of decreased belowground carbohydrate allocation.